Gallbladder metastasis from hepatocellular carcinoma: Report of a case and review of literature - Wakasugi, Masaki (Elsevier, 2012)
INTRODUCTION: The incidence of metastasis of hepatocellular carcinoma (HCC) to the gallbladder is low. Here, we report a case of HCC with metastasis to the gallbladder and discuss the pattern of spread and the treatment. PRESENTATION OF CASE: A 74-year-old man was diagnosed with advanced hepatocellular carcinoma. Computed tomography and magnetic resonance imaging demonstrated a tumor in the right lobe of the liver with a thrombus in the bifurcation of the portal vein. Because intraoperative ultrasonography showed portal vein tumor thrombosis from the main tumor reaching the umbilical portion, we performed only a cholecystectomy for the elimination of postoperative cholecystitis. Pathological examination showed gallbladder vein tumor thrombosis from poorly differentiated hepatocellular carcinoma. DISCUSSION: A preoperative diagnosis of metastatic HCC to the gallbladder is difficult because there are no specific findings in the imaging tests. Cancer cells in the liver were thought to migrate to the gallbladder via the connection between the portal system and the cholecystic veins, and grow in the lumen of the veins in our case. The survival rate, in all reported cases including the present case, was increased in patients who underwent radical resection, compared to patients who underwent palliative surgery. CONCLUSION: The resection of metastatic HCC to the gallbladder might appear to prolong survival.